'The data is gold, and we are the gold-diggers': whiteness, race and contemporary academic research in eastern DRC. Issue 3 (1st September 2020) - Marchais, Gauthier; Bazuzi, Paulin; Amani Lameke, Aimable
Abstract : The boom of the humanitarian and development industry in eastern Democratic Republic of the Congo (DRC) and the demand for qualitative and quantitative research that has accompanied it have created a novel political economy of academic research in the region. An array of research associations and private data collection firms have emerged to respond to the international demand by Western universities and research projects. Like many industries operating on the continent, academic research has a racial dimension, which is rarely reflected upon, in part because it is often invisible to white Western researchers. This paper reflects on the creation and evolution of a non-profit association specialized in the collection of data in conflict-affected areas of eastern DRC. The research association was conceived by its Congolese and European founders as an enclave against the racism that pervades professional relations in the region, an experiment upheld by a collective commitment to academic research and an egalitarian ethos. Written from the perspective of three of its founding members, this paper analyses how racialized discursive repertoires and cognitive biases (re)appeared within the organization. We argue that these repertoires and biases serve to activate a particular mode of production, based on racial and geographic inequalities in working conditions and prospects. We interrogate the relationship between race and the system of production underpinning contemporary research, and show that, far from solely being a remnant of the colonial era, race constitutes a resource that can be tapped into, particularly in a context where empirical data, competition for funding, and 'value for money' are increasingly becoming the norm.